Stock investment funds in Brazil: performance and management expertise - Matos, Paulo Rogério Faustino (2012)
This article analyzes the stock investment fund market in Brazil and proposes dynamic rankings constructed from different risk-return metrics, during the period from 1998 to 2009. We find an uncommon level of persistence, mainly among the best performing funds, due to the expertise of the managers. The quadrimestral rebalancing of the portfolios based on these rankings permits inferring that in scenarios characterized as economic booms or recovery of financial markets, the strategies with equal participation in winner funds provides significantly higher average monthly gains, reduction of risk associated with diversification and consequently enhanced performance in relation to market or sector benchmarks. This evidence is robust to the use of different performance metrics for fund selection, indicating that active investors in winning funds demand good performance not only in terms of the Sharpe ratio, but also with respect to other metrics, such as the Treynor, Calmar and Sortino ratios. In these optimistic scenarios, only the industrial sector index (INDX) provided returns compatible with those of these fund’s portfolios. However, during periods of crisis, no strategy involving the funds managed to provide hedge levels characteristic of the electric energy sector index (IEE), so it can be said that the majority of investing strategies are dominated in gain-risk criteria by sector or market indexes, with the exception of value-weighted portfolios composed of losing funds, a signal that the usual passive investors in large funds indexed to the Ibovespa can be presenting a greater level of inertia.